William H. Emory papers - Emory, William H. (William Hemsley), 1846-1917.
Correspondence, journal, conduct and rating books, photographs, and printed matter relating to Emory's command of the U.S. cruiser Yosemite during the Spanish-American War. Correspondents include George William Coffin, John Davis Long, Cyrus E. Lothrop, and Truman Handy Newberry.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Coffin, George William, -- 1845-1899 -- Correspondence; Long, John Davis, -- 1838-1915 -- Correspondence; Lothrop, Cyrus E., -- 1861-1913 -- Correspondence; Newberry, Truman Handy, -- 1864-1945 -- Correspondence; United States. -- Navy -- Officers; Yosemite (Cruiser); Spanish-American War, 1898 -- Naval operations; Naval officers